Autism in adult and juvenile delinquents: a literature review - A. X. Rutten; R. R. J. M. Vermeiren; Ch. Van Nieuwenhuizen (BMC, 2017)
Abstract Background Here we present an overview of the literature on autism in adult and juvenile delinquents. We analyzed both the prevalence of autism spectrum disorders (ASD) in groups of delinquents and the prevalence of offending in people with ASD. There is a high prevalence of psychiatric disorders amongst people in custody, but there is disagreement about the prevalence of ASD in this population. Some studies have found overrepresentation of people with ASD in forensic populations whereas others have found that people with ASD have a similar rate of offending to the general population. Methods We carried out a systematic search of literature published between 1990 and 2016 and identified studies on the co-occurrence of autism and delinquency using standard search engines. Results The prevalence of delinquency in the ASD population varied from 5 to 26%, whilst ASD was found in 2-18% of the forensic populations studied. The reported prevalence of ASD in delinquents and of offending in people with ASD varied widely. This might be due to the use of different diagnostic instruments, the diversity of the samples, the high rate of comorbid psychiatric disorders and the various types of offending behavior. Conclusions We cannot conclude from our analysis that people with ASD are more likely to offend than the general population.